2021
DOI: 10.1161/circinterventions.120.009863
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Compared With Delayed Percutaneous Coronary Intervention for Patients With ST-Segment–Elevation Myocardial Infarction Presenting ≥12 Hours After Symptom Onset Is Not Associated With Improved Clinical Outcome

Abstract: Background: The role of immediate percutaneous coronary intervention (PCI; door-to-balloon time ≤90 minutes) in patients with ST-segment–elevation myocardial infarction who present ≥12 hours after symptom onset is still obscure. We sought to explore the clinical outcomes of immediate PCI in patients with ST-segment–elevation myocardial infarction depending on presentation time. Methods: Using the Korea Acute Myocardial Infarction Registry, a nationwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…[21][22][23][24][25] In KAMIR-NIH, 2-year rates of all-cause death and MACE were 12.5% and 13.4% in late presenters (n=599), and 13.6% and 11.3% in very later presenters (n=265), respectively. 27 In line with our data, very late presenters were older, had higher NT-pro-BNP levels, worse renal function and worse LVEF, but even unadjusted crude outcomes were not substantially worse in these very late presenters, all undergoing PCI. 27 It has been established that in acute myocardial infarction, fully salvageable myocardium is a function of time with a narrow window as low as <3 hours.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[21][22][23][24][25] In KAMIR-NIH, 2-year rates of all-cause death and MACE were 12.5% and 13.4% in late presenters (n=599), and 13.6% and 11.3% in very later presenters (n=265), respectively. 27 In line with our data, very late presenters were older, had higher NT-pro-BNP levels, worse renal function and worse LVEF, but even unadjusted crude outcomes were not substantially worse in these very late presenters, all undergoing PCI. 27 It has been established that in acute myocardial infarction, fully salvageable myocardium is a function of time with a narrow window as low as <3 hours.…”
Section: Discussionsupporting
confidence: 89%
“…27 In line with our data, very late presenters were older, had higher NT-pro-BNP levels, worse renal function and worse LVEF, but even unadjusted crude outcomes were not substantially worse in these very late presenters, all undergoing PCI. 27 It has been established that in acute myocardial infarction, fully salvageable myocardium is a function of time with a narrow window as low as <3 hours. [28][29][30] In contrast, even in patients with totally occluded infarct arteries, substantial (>50%) myocardial salvage could be achieved with late reperfusion after 12-72h.…”
Section: Discussionsupporting
confidence: 89%
“…There were various MACE rates that have been reported previously. Data taken from Korea Acute Myocardial Infarction Registry revealed that MACE rate at 2-year follow up for different group of STEMI patients who underwent delayed PCI was ranged from 13.4% to 17.9% (34). In a patient-level pooled data from prospective randomised stent trials, 1-year MACE rate was 7.9% while the overall 5-year rate of MACE was 16.1% (12).…”
Section: Discussionmentioning
confidence: 99%